# supply - price equation

• Apr 3rd 2011, 06:19 AM
hansfordmc
supply - price equation
Am I doing this correctly - thanks.

price: 2.27
supply: 7200

price: 2.36
supply: 7600

p = mx + b
-----------------
m = (2.36 - 2.27)/(7200-7600) = .09/-400 = -399.91
p = .09x - 399.91
• Apr 3rd 2011, 07:13 AM
Unknown008
No, if you take the first one, you need to take the first one.

What is mean is:

$m = \dfrac{2.36 - 2.27}{7600 - 7200}$

First is 2.36, hence, in the denominator, you get the value associated with 2.36, which is 7600 first.

Similarly, if you had put 2.27 first, then in the denominator, you will have 7200 - 7600.
• Apr 3rd 2011, 07:22 AM
SpringFan25
Quote:

Am I doing this correctly - thanks.

price: 2.27
supply: 7200

price: 2.36
supply: 7600

p = mx + b
-----------------
m = (2.36 - 2.27)/(7200-7600) = .09/-400 = -399.91
p = .09x - 399.91

the formula for a gradient is:
(change in p) / (change in x)

m = (2.36 - 2.27)/(7600 - 7200)

this evaluates to
.09/400 = 0.00023

So you know
p=0.000225x + b

Now you can sue a pair of points to find b. You know that on possible outcome is
price=2.27
supply=7200

so:
2.27=0.000225 * 7200 + b
2.27= 1.62 + b
0.65 = b

So
p = 0.00023x + 0.65
• Apr 3rd 2011, 07:22 AM
hansfordmc
That makes sense - thanks.
• Apr 3rd 2011, 07:28 AM
hansfordmc
So now I have:

P - 2.36 = .09x - .000225
P = .09x - 8.99

does this appear correct?
• Apr 3rd 2011, 07:32 AM
hansfordmc
@SpringFan25 - sorry, I didn't see your post before posting my last response. I'm studying what you're doing now - thanks